The Effect of ICARE Model Assisted by Virtual Practicum on Students’ Science Process Skills in Traveling Wave and Stationary Wave Materials - Nuraeni, Nisa; Aripin, Aripin; Makiyah, Yanti Sofi (JPPS (Jurnal Penelitian Pendidikan Sains), 2024)
Objective: This study aimed to analyze the effect of the ICARE model assisted by virtual labs on students' science process skills. Method: This research was a quasi-experiment using a posttest-only control group design. The sample consisted of 35 students of XI MIPA 4 and 35 students XI MIPA 6 MAN 2 Tasikmalaya Regency.  Data collection was carried out through an essay-shaped science process skills test consisting of 6 questions which were analyzed using the t test.Results:  Hypothesis test using a t-test at the significance level () obtained tcount  ttable where 3.35 > 1.67 so that   was accepted and  was rejection. Therefore, the research findings show that the ICARE model assisted by virtual practicum has an effect on students' science process skills on the material of traveling waves and stationary waves. Novelty: Innovation in this study was that students applied the material learned with the help of virtual practicum to train science process skills.